Ethnomathematics: Arithmetic and Discrete Mathematics Concepts in Batik Sidomukti Solo - Kholid, Muhammad Noor; Husodo, Herlang Duta (Mathematics Education Journal, 2025)
Ethnomathematics is the study of the relationship between mathematics and culture and its application in everyday life. Batik, as one of Indonesia’s most iconic cultural heritages, contains patterns and structures rich in mathematical ideas, making it a relevant and engaging case study for mathematics education. Batik has the potential to contextualize abstract mathematical concepts through visual and cultural elements. This study specifically focuses on Batik Sidomukti, a classical batik from Surakarta, which is characterized by its distinctive curved patterns known as Isen Ukel. Isen Ukel refers to ornamental curved or spiral lines used as filler patterns, which traditionally symbolize life, continuity, and aesthetic harmony in Javanese batik art. To explore the mathematics concepts embedded in Batik Sidomukti, this study employed a qualitative approach using ethnography and Ethnomathematics Guiding Questions. Ethnography is suitable for this context as it allows for an in-depth understanding of the cultural and artistic context of batik making, including the symbolic meanings and design structures. Data were collected through field observation, motif documentation, and literature review. This approach enabled the researcher to identify and analyze arithmetic and discrete mathematics elements present in the batik designs. For instance, modular and tiling arithmetic are reflected in the repetitive and structured arrangement of motifs, while discrete mathematics is represented through graph theory and combinatorics. The application of combinatorics, in particular, contributes to the aesthetic appeal and design variation of Batik Sidomukti. These findings highlight the significance of ethnomathematics in bridging cultural heritage and mathematics education. Batik motifs, especially Batik Sidomukti, are not only traditional artworks passed down through generations, but also a rich source of inspiration for developing culturally relevant mathematics instruction.